2020
DOI: 10.1891/jcpsy-d-20-00001
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy: A Systematic Literature Review of Prevention and Intervention Programs for Mental Health Difficulties in Children and Young People

Abstract: BackgroundAcceptance and commitment therapy (ACT) is increasingly being used to treat mental health difficulties, however there is a paucity of reviews concerning ACT with children.AimTo examine the literature about ACT interventions for child and adolescent mental well-being.MethodsSearches for articles reporting on ACT interventions to prevent/reduce child mental health difficulties were undertaken. Methodological quality was assessed and a narrative synthesis was used to summarize findings about mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Students with high levels of psychological flexibility are less likely to conceptualize or experience stereotypes of vocational student identity, less likely to develop a state of avoidance when perceiving external discrimination, and more willing to accept the present situation and take positive action to do something more meaningful. Psychological flexibility is a core component of ACT and is a skill that can be developed through intervention ( Harris and Samuel, 2020 ). Therefore, ACT should be incorporated into the career planning curriculum for higher vocational students to enhance psychological flexibility and promote active career exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students with high levels of psychological flexibility are less likely to conceptualize or experience stereotypes of vocational student identity, less likely to develop a state of avoidance when perceiving external discrimination, and more willing to accept the present situation and take positive action to do something more meaningful. Psychological flexibility is a core component of ACT and is a skill that can be developed through intervention ( Harris and Samuel, 2020 ). Therefore, ACT should be incorporated into the career planning curriculum for higher vocational students to enhance psychological flexibility and promote active career exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the era of increasing technological level, the substitution effect of technological progress on labor force is gradually emerging ( Blien and Sanner, 2014 ). Many people lost their jobs during the COVID-19 lockdown ( Harris and Samuel, 2020 ). The outbreak of the COVID19 pandemic has increased the unemployment rate in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Harris and Samuel analyzed the relevant literature on ACT interventions in adolescent mental health. They found that ACT contributes to addressing adolescent mental health problems; however, more insight is needed to the progress and changes of action to determine the role of ACT in increasing psychological flexibility ( Harris and Samuel, 2020 ). Given this recent call to action, it is necessary to continue and expand ACT research.…”
Section: Introductionmentioning
confidence: 99%
“…IPT is less studied than CBT but shows promising results for anxiety disorders (although with no superiority compared to other bona fide therapies) (Markowitz et al, 2014). Other treatment approaches such as psychodynamic psychotherapy, acceptance and commitment therapy, or mindfulness have also been used for anxiety and depressive disorders Chi et al, 2018;González-Valero et al, 2019;Harris and Samuel, 2020;.…”
Section: Introductionmentioning
confidence: 99%